[OP.8D.05] LAYER-SPECIFIC QUANTIFICATION OF MYOCARDIAL DEFORMATION MAY DISCLOSE THE SUBCLINICAL SYSTOLIC DYSFUNCTION AND THE MECHANISM OF RESERVED EJECTION FRACTION IN HYPERTENSIVE PATIENTS. (September 2016) - XU, T.; Sun, J.P.; Lee, A.P.; Yang, Y.; Yang, X.S.; Li, Y.; Yu, C.; Wang, J.G
Abstract : Objective: Hypertension (HTN) leads to left ventricular (LV) remodeling, which results in diastolic dysfunction in the presence of preserved ejection fraction (EF). The goal of this study was to explore the subclinical left ventricular systolic dysfunction and the mechanism of preserved EF using layer-specific quantification of myocardial deformation in patients with HTN. Design and method: The routine 2D (frame rate > 50 Hz) data sets were acquired using GE E9 system in 120 hypertensive patients (73 male, 54 ± 13years, blood pressure =165 ± 20/ 96 ± 16 mmHg) and 120 age and gender matched normal subjects (124 ± 9/80 ± 8mmHg). The relative wall thickness (RWT) was calculated as the sum of anterior septal and posterior wall thickness divided by the LV end-diastolic dimension. Analysis of 2D strain was performed by EchoPac software. The RWT, LV mass index, and EF, as well as the values of 2D LV global and layer longitudinal and circumferential strains were all analyzed. Results: The LVEF was normal in all HTN patients. The RWT and LV mass index were higher in HTN than normal group (0.40 ± 0.07 vs 0.35 ± 0.03, p < 0.0001; 91 ± 26 vs 84 ± 8 g/m2, p < 0.0001). The absolute value of layer and global longitudinal strain was significantly decreased (−24 ± 3vs −26 ± 3 %, p < 0.0001;. −21 ± 3vs −23 ± 3%, respectively, p < 0.0001) and global circumferential strain (−40 ± 6vs −35 ± 5 %, −31 ± 7 vs −27 ± 4 % respectively, p < 0.0001), and the LV twist (23 ± 5 vs 18 ± 6 degree, p < 0.0001) were higher in HTN group than in normals. Conclusions: This study revealed that hypertension results in increased RWT and LV mass. The absolute value of layer and global longitudinal strain was significantly decreased in HTN patients than control group, which may implicate the early systolic dysfunction due to the endomyocardium function impaired. The absolute value of circumferential strain, and LV twist were significantly increased, which may be a compensatory mechanism to maintain LVEF.